Morbus Niemann-Pick Typ C: Klinik, Diagnostik und Therapie - Mengel, Eugen; Ebinger, Friedrich; Runz, Heiko (Monatsschrift Kinderheilkunde, 2012)
Niemann-Pick disease type C (NPC) is a rare, neurovisceral lysosomal storage disease. A deficiency in the NPC1 or NPC2 protein results in impaired digestion and subsequent accumulation of plasma membrane lipids in the lysosomes. Visceral signs and symptoms may occur years before the onset of neurological manifestations. The clinical phenotype of NPC is, however, determined by the onset and progression of neurodegeneration. Neurological manifestations of NPC can be treated using substrate reduction therapy with miglustat. A clinical study showed that 72% of NPC patients treated with miglustat experienced stabilization or slowed progression of the disease. At present, miglustat is the only approved treatment option in Europe for NPC patients with neurological symptoms. Monitoring of disease progression and response to treatment with miglustat should be conducted with regular follow-up and standardized documentation. Additional research on the molecular basis and clinical course of NPC will be required in order to provide affected patients with an early targeted and efficacious treatment to curtail this normally progressive disease.
First online 23 December 2011
Gesehen am 29.11.2018